KANIEN’KEHA / MOHAWK INDIGENOUS LANGUAGE REVITALISATION EFFORTS IN CANADA - Gomashie, Grace A. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
This paper gives an overview of ongoing revitalisation efforts for Kanien’keha / Mohawk, one of the endangered Indigenous languages in Canada. For the Mohawk people, their language represents a significant part of the culture, identity and well-being of individuals, families, and communities. The endangerment of Kanien’keha and other Indigenous languages in Canada was greatly accelerated by the residential school system. This paper describes the challenges surrounding language revitalisation in Mohawk communities within Canada as well as progress made, specifically for the Kanien’keha / Mohawk language.